2016
DOI: 10.1038/srep32344
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibition rapidly affects in a reversible manner distinct features of birdsong

Abstract: Recent evidence has implicated steroid hormones, specifically estrogens, in the rapid modulation of cognitive processes. Songbirds have been a useful model system in the study of complex cognitive processes including birdsong, a naturally learned vocal behavior regulated by a discrete steroid-sensitive telencephalic circuitry. Singing behavior is known to be regulated by long-term actions of estrogens but rapid steroid modulation of this behavior has never been examined. We investigated if acute actions of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…In adult male zebra finches, long-term aromatase inhibition leads to suppressed courtship displays, including song production (Walters and Harding, 1988). More recent studies have found that neuroestrogen production also appears to acutely facilitate song production in adult zebra finches (Remage-Healey et al, 2009;Alward et al, 2016). Our data expand on this understanding that acute suppression of E2 production constrains singing to now include developing male songbirds.…”
Section: Brain Estrogen Synthesis and Song Production In Developing Ssupporting
confidence: 71%
See 2 more Smart Citations
“…In adult male zebra finches, long-term aromatase inhibition leads to suppressed courtship displays, including song production (Walters and Harding, 1988). More recent studies have found that neuroestrogen production also appears to acutely facilitate song production in adult zebra finches (Remage-Healey et al, 2009;Alward et al, 2016). Our data expand on this understanding that acute suppression of E2 production constrains singing to now include developing male songbirds.…”
Section: Brain Estrogen Synthesis and Song Production In Developing Ssupporting
confidence: 71%
“…Systemic administration: Birds in this experiment received an oral administration of either FAD or saline every other day for 20 days immediately following tutoring. Initially, we measured singing rates of systemically-treated animals before (<40 dph) and during the tutoring period (40 -60 dph) as global inhibition of estrogen synthesis in adult songbirds can reduce song production (Alward et al, 2016). Pre-tutoring, birds sang at comparable rates independent of the time of day or future treatment group (treatment: F(1, 13) = 2.466, p = 0.140; time of day: F(1, 13) = 1.797, p = 0.203; treatment * time of day: F(1, 13) = 0.719, p = 0.412; Fig.…”
Section: Song Learning Is Unaffected By Global Estrogen Synthesis Inhmentioning
confidence: 99%
See 1 more Smart Citation
“…We were also surprised to see that chronic exemestane treatment in females caused some females to produce 1-2 repeated syllables in a song-like manner, even though they had atrophied song nuclei. Prior studies have shown that acute aromatase inhibition can suppress the rate of singing in zebra finches and canaries (Alward et al, 2016;Vahaba et al, 2019;Walters and Harding, 1988), but no changes in song learning acuity have been reported (Merten and Stocker-Buschina, 1995;Vahaba et al, 2019). Perhaps the more potent and longterm application of the estrogen inhibitor we used revealed an unknown involvement of estrogen in vocal learning.…”
Section: Discussionmentioning
confidence: 83%
“…Prior studies that have used fadrozole, a drug that inhibits aromatase from converting androgens to estrogens, did not reveal any impacts on male song development either behaviorally or anatomically (Merten and Stocker-Buschina, 1995;Wade and Arnold, 1994). However, fadrozole was later found to effect song behavior and aromatase activity only briefly within 30 minutes of injection; the effects were lost after 4 hours (Alward et al, 2016). It was also found that fadrozole can stabilize the aromatase protein, which is then followed by increased estrogen synthesis after drug clearance, causing a "rebound effect" (Harada and Hatano, 1998).…”
Section: Introductionmentioning
confidence: 92%